(untitled) (American Journal of Society and Law, 2025)
If we look at the criminal side of the protection of public property, we can say that there are laws and legal mechanisms in Afghanistan’s criminal law (as a type of the legal system) which would be used to deter and punish offenders who commit crimes against public property. This kind of protection is one of the best and most important ways to protect public property. Nonetheless, despite the presence of these legal provisions, there are challenges in the enforcement of laws against public property offenses which include weak institutional capacity, corruption, and lack of public awareness on the legal implications of these offenses. Addressing these challenges is crucial to enhancing the legal framework’s efficiency. The present study examines applicable legal concepts using a descriptive-analytical approach of research method and library data collection. The analysis also includes a comparative approach to showcase how other jurisdictions address similar issues and suggestions for best practices which could be considered in relation to Afghanistan. The results demonstrate that in Afghanistan’s legal system, public property is defined as assets that are allocated for the common use and well-being of society. No criminal penalty is more effective than others for unlawful penetration of such property, including capital punishment, imprisonment, fine and damage, depending on the severity and nature of the crime. Criminal policy is the systematic approach that enables these criminal protections to be enforced, and against which the perpetrators can be held accountable. Some sort of stringent yet efficiently executed penal provision coupled with institutional mechanisms and public legal awareness campaigns, however, would be required to bring down the numbers of crimes against public property to further protect national wealth and resources. Moreover, the adoption of relevant international best practices and stronger legal oversight mechanisms could go a long way in enhancing the protection of public property in Afghanistan legal system.